Culture of antibiotic use in Kosovo - an interview study with patients and health professionals - Jakupi, Arianit (Pharm Pract (Granada), 2019)
BACKGROUND: Kosovo is a new state and has a high consumption of antibiotics in relation to other European countries. Existing quantitative studies have shown that practices exist that is not optimal when it comes to antibiotic use in Kosovo, this includes citizens’ use of antibiotics, pharmacy practices of selling antibiotics without prescriptions and physicians’ prescribing behaviours. To address these problems, there is a need for a deeper understanding of why antibiotics are handled in a suboptimal way. OBJECTIVE: The objective was to explore antibiotic users’, community pharmacists’ and prescribers’ attitudes towards, experiences of, and knowledge about antibiotics in Kosovo. METHODS: Semi-structured interviews were conducted with patients who recently received an antibiotic prescription for an upper respiratory tract infection (URTI), patients who recently received antibiotics for a URTI without a prescription, community pharmacists, and physicians. Interviews were recorded, translated into English, and analysed using deductive content analysis. RESULTS: In total, 16 interviews were conducted in the period from 2015-2016. Five themes were identified: Obtaining antibiotics, Choice of antibiotics, Patient information, Patients’ knowledge and views on when to use antibiotics, and Professionals’ knowledge and attitudes towards antimicrobial resistance. Antibiotics were sometimes obtained without a prescription, also by patients who currently had received one. The specific antibiotic could be chosen by a physician, a pharmacist or the patient him/herself. Former experience was one reason given by patients for their choice. Patients’ knowledge on antibiotics was mixed, however health professionals were knowledgeable about e.g. antimicrobial resistance. CONCLUSIONS: There is currently a culture of antibiotic use in Kosovo, including attitudes and behaviours, and hence also experiences, which is possibly underlying the high consumption of antibiotics in the country. The culture is reproduced by patients, pharmacists and physicians. There is, however, an awareness of the current problematic situation among practitioners and policy makers; and as Kosovo is a new country, opportunities to effectively tackle antimicrobial resistance exist.